Factors influencing the adoption of cloud computing in SME: A systematic review - Alkawsi, G.A. (Institute of Electrical and Electronics Engineers Inc., 2016)
The main purpose of this paper is to review the literatures on the adoption of Cloud Computing by SMEs in order to learn the current state of Cloud Computing studies and identify gaps for future research. Twenty-two articles were reviewed and analyzed from various journals and conference proceedings that were published on Cloud Computing adoption, acceptance, and diffusion. Findings revealed that there are growing numbers of studies in the adoption of Cloud Computing from different perspectives, yet there is a lack of theoretical and empirical studies in the field. Findings also indicated that there are only few articles evaluated the organizational perspective of Cloud Computing adoption in SMEs, while the majority of studies discussed operational and technical issues. Furthermore, this review observed various factors influencing the adoption of Cloud computing, which were addressed based on the four main criteria of the acceptance and diffusion of technological innovations, which are individual, organization, technology and environment. Â© 2015 IEEE.